Economic policy uncertainty, monetary policy, and housing price in China - Sen Wang; Yanni Zeng; Jiaying Yao; Hao Zhang (Journal of Applied Economics, 2020)
This paper analyzes the impact of macroeconomic variables on house price volatility under different regimes of policy uncertainty, incorporating the Economic Policy Uncertainty Index and several Chinese macroeconomic data sets for the period from 1999 to 2014. We adopt a logistic smooth transition vector autoregressive model and a generalized impulse response function. The results show that macroeconomic progress leads to house price growth, which is augmented by policy uncertainty. In addition, the effect of macroeconomic shocks on house price volatility varies under different regimes of policy uncertainty. We find that shocks are asymmetric under regimes of high and low policy uncertainty. Under a high policy uncertainty regime, expansionary quantitative monetary policy can facilitate house price growth, whereas a contractionary monetary policy gives rise to an enduring "Home Price Puzzle," which makes it difficult to regulate house prices.
Keywords: 330; Chinese market; Economic policy uncertainty; house price volatility; LSTVAR model